Sven Skjenneberg Doctor Honoris Causa - Rehbinder, Claes; Danell, Öje (Rangifer, 1993)
In August 28, 1993, Sven Skjenneberg was conferred the degree of Veterinary Medical Doctor Honoris Causa at the Swedish University of Agricultural Sciences, Uppsala, Sweden.